2013
DOI: 10.1186/1752-153x-7-169
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the traditional Indian Shodhana and Chinese processing methods for aconite roots by characterization and determination of the major components

Abstract: BackgroundAconitum is an indispensable entity of the traditional medicine therapy in Ayurveda and Traditional Chinese medicine (TCM), in spite of its known fatal toxicity characteristics. The prolonged use of this drug, irrespective of its known lethal effects, is governed by the practice of effective detoxification processes that have been used for decades. However, the processing methods of Ayurveda and TCM are different, and no comparative study has been carried out to evaluate their differences.The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Ethanolic extract of A. heterophyllum contains alkaloids, steroids, saponins, glycoside and phenolic compounds [46]. The phytochemical constituents of root were reported that to be having stabilizing on the lysosomal membrane both in vitro and In vivo are flavonoids, tannins and saponins [47,48]. Freidelin (terpinoid) present in the plant leaves is found to have antioxidant, free radical scavenging and hepatoprotectiive [49].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanolic extract of A. heterophyllum contains alkaloids, steroids, saponins, glycoside and phenolic compounds [46]. The phytochemical constituents of root were reported that to be having stabilizing on the lysosomal membrane both in vitro and In vivo are flavonoids, tannins and saponins [47,48]. Freidelin (terpinoid) present in the plant leaves is found to have antioxidant, free radical scavenging and hepatoprotectiive [49].…”
Section: Discussionmentioning
confidence: 99%
“…The plants belong to the same genus but different species, and a comparative study would help identify the similarities and dissimilarities in their essential oil content and other secondary metabolites. In our previously published studies, we have identified how plant species belonging to different species, but the same genus, can serve as qualitative substitutes for each other based upon their detailed metabolomics analysis [20][21][22][23]. Several studies have reported the asarone content determination and pharmacological studies of Acorus species [24][25][26][27].…”
mentioning
confidence: 99%
“…Detoxification of the tubers was done using either water, or cow or goat milk according to the traditional Ayurvedic method i.e., shodhana samaskara [18,19] and extraction was performed using chloroform as per our previous study [12]. Different solvents e.g., n-hexane, chloroform, methanol and water were used for extraction and chloroform extract was found to contains maximum percentage yield hence was used for further investigation [20].…”
Section: Detoxification and Extractionmentioning
confidence: 99%